Women shaping the south creating and confronting change - Southern Conference on Women's History 2003 : Athens, Ga.); Boswell, Angela, 1965-; McArthur, Judith N.; ebrary, Inc. (Columbia : University of Missouri Press, 2006)
"Expanded from papers presented at the Sixth Southern Conference on Women's History, this collection demonstrates how women of different races and classes transformed the South during its most crucial turning points, including post-Revolution, Civil War, Jim Crow era, World War I, and the civil rights movement"--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Women -- Southern States -- History -- Congresses; Southern States -- History -- Congresses; Electronic books